First report of Fusarium species at nesting sites of endangered sea turtles in Terengganu and Melaka, Malaysia - Siti Nordahliawate Mohamed Sidique; Nurul Farizah Azuddin; Juanita Joseph (Penerbit Universiti Kebangsaan Malaysia, 2017)
In recent years, turtle eggs incubated in situ or in protected hatcheries in Malaysia have been reported to show symptoms and signs of fungal colonisation. However, there are no studies addressing this problem and potential relationship with frequent hatching failures. We identified Fusarium species from nesting sites of green turtle (Chelonia mydas) and hawksbill turtle (Eretmochelys imbricata) situated in Terengganu and Melaka, as well as the environments surrounding those sites. The eggs were incubated on the nesting beach (in situ) or relocated to the beach hatchery and styrofoam boxes (ex situ) in Peninsular Malaysia. Samples were collected from infected eggs, sand, plant roots and debris around the egg chambers. One-hundred and six strains of Fusarium spp. were isolated. They were identified morphologically as member of the Fusarium solani species complex (FSSC, 101 strains), F. oxysporum (four strains) and F. proliferatum (one strain). We conducted phylogenetic analysis based on nucleotide sequences of translation elongation factor 1-alpha gene (TEF-1α). The strains of the FSSC were further separated into three lineages, F. falciforme, F. lichenicola and F. keratoplasticum. This is the first report on Fusarium species isolated from symptomatic green and hawksbill turtle eggs in Peninsular Malaysia. Fusarium colonisation in sea turtle nests poses a serious risk to the survival of endangered sea turtles in Malaysia. It is, therefore, important to examine the nature of such colonisation and their relationship to hatching failures of the turtles in Malaysia or elsewhere in the region to mitigate pathogenic fungi impact.